Democracy / Participation-Based Corporate Social Responsibility Management Improves Public Welfare in Indonesia (International Journal of Scientific Research and Management (IJSRM), 2021)
CSR is a responsibility that must be implemented by every company, where the company’s responsibility is not only on the financial condition. But corporate responsibility (CSR) is also related to all stakeholders included their family employees. The existence of a company can have two impacts, namely positive and negative, therefore the company needs to prevent negative impacts that may arise and can interfere with the company’s operations and community activities. This, CSR is very necessary to be implemented in every company. This research uses qualitative research and uses a deductive approach. The results of this study indicate that the implementation of CSR is indispensable in a company, the variable of participation democracy takes part in the establishment of the company and the level of welfare of the Indonesian people is one of the impacts of the success of a company in promoting the concept of CSR.